2013
DOI: 10.1002/jor.22497
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of slow, uphill and fast, level walking on lower extremity biomechanics and tibiofemoral joint loading in obese and nonobese adults

Abstract: We determined if slow, uphill walking (0.75 m/s, 6°) reduced tibiofemoral (TF) loading compared to faster, level walking (1.50 m/s) in obese and nonobese adults. We collected kinematic, kinetic, and electromyographic data as 9 moderately obese and 10 nonobese participants walked on a dual-belt instrumented treadmill. We used OpenSim to scale a musculoskeletal model and calculate joint kinematics, kinetics, muscle forces, and TF forces. Compressive TF forces were greater in the obese adults during both speed/gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 30 publications
3
47
1
Order By: Relevance
“…For example, thorough biomechanical evaluation suggests that slow uphill walking may be appropriate exercise for obese individuals at risk for musculoskeletal pathology or pain. 130 The functional and structural restrictions produced by the extra loading of the locomotor system in patients with increased BMIs resulted in an anomalous biomechanical pattern during locomotor tasks, producing abnormalities in other connective tissue structures (tendons, ligament, fasciae, bursae) and increased frequency of injuries, including fractures. 131,132 Occupational medicine literature has established that obese men are at increased risk of multiple rib fractures, and obese women are at greater risk of fracture in the vertebral column, leg, ankle, and humerus and at lesser risk of wrist, hip, and pelvis fractures.…”
Section: Biomechanical and Structural Mechanismsmentioning
confidence: 99%
“…For example, thorough biomechanical evaluation suggests that slow uphill walking may be appropriate exercise for obese individuals at risk for musculoskeletal pathology or pain. 130 The functional and structural restrictions produced by the extra loading of the locomotor system in patients with increased BMIs resulted in an anomalous biomechanical pattern during locomotor tasks, producing abnormalities in other connective tissue structures (tendons, ligament, fasciae, bursae) and increased frequency of injuries, including fractures. 131,132 Occupational medicine literature has established that obese men are at increased risk of multiple rib fractures, and obese women are at greater risk of fracture in the vertebral column, leg, ankle, and humerus and at lesser risk of wrist, hip, and pelvis fractures.…”
Section: Biomechanical and Structural Mechanismsmentioning
confidence: 99%
“…These tasks may also be relevant to clinical, rehabilitation or sport applications. For instance, toe walking is observed in patients with various neurologic and developmental abnormalities (Oetgen and Peden, 2012), backward locomotion is used increasingly in sports and rehabilitation (Hoogkamer et al, 2014) and uphill walking may be appropriate exercise for obese individuals at risk for musculoskeletal pathology or pain (Haight et al, 2014). We used the recordings from 26 leg muscles (including intrinsic foot muscles that have not typically been considered) to reconstruct spinal motor outputs with specific interest in identifying common and idiosyncratic features across locomotor gaits.…”
Section: Introductionmentioning
confidence: 99%
“…As body mass index (BMI) increases, gait speed decreases [7]. Past studies of knee joint kinematics mainly focused on sagittal and coronal plane motions, i.e., knee joint flexion/extension [5, 810] and varus/valgus rotation [9, 10]. Even so, there is no clear consensus on knee joint kinematics in obese individuals during walking.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, there is no clear consensus on knee joint kinematics in obese individuals during walking. For example, Haight et al[8] reported that obese individuals walked with a less flexed knee during the stance phase compared to non-obese individuals. Vismara et al [11] concluded that the range of knee flexion excursion during gait was not significantly different than a healthy group.…”
Section: Introductionmentioning
confidence: 99%